Influence of Work Environment and Discipline on the Performance of Non-Naked Health Employees of the Dr. Lung Hospital Goenawan Partowidigdo Cisarua Bogor - Faizal; Erni Yuningsih; Yulianingsih (MultiTech Publisher, 2023)
This research aims to determine and analyze the influence of the work environment and discipline, both simultaneously and partially, on the performance of non-health workers at Pulmonary Hospital Dr. Goenawan Partowidigdo Cisarua Bogor. This research design uses descriptive and verification research methods. The sampling technique uses non-probability sampling techniques. The number of respondent was 61 people. The subject of this research were non-health workers at Pulmonary Hospital Dr. Goenawan Partowidigdo Cisarua Bogor, and the object of this research is the work environment, discipline and employee performance. The tools used in this analysis are multiple regression analysis, multiple correlation analysis, coefficient of determination analysis, and hypothesis testing (F test and t test). The research results show that employee responses to work environment variables are in the good category, discipline is in the good category, and employee performance is in the good category. Partially or simultaneously, the work environment, discipline and employee performance have a significant and positive influence on the performance of non-health workers at Pulmonary Hospital Dr. Goenawan Partowidigdo Cisarua Bogor.